Growth performance of rice in zinc deficit soils added with zinc, phosphorous and lime - Soltani, Shahram Mahmoud (2015)
Zinc (Zn) is the most limiting micronutrient that its deficiency is a widespread nutritional disorder of tropical wetland rice. The addition of Zn, lime, and phosphorous (P) influences the amounts of plant-available Zn and rice growth. The present study was undertaken to assess native and applied Zn fractions of six tropical paddy soil series under different amendments (P fertilizer, liming and Zn fertilizer additions), and their effect on the soil Zn status, growth, yield, yield components and quality of rice. The Zn deficient soil series were sampled from the topsoil of Kedah and Kelantan paddy fields for incubation (six), glasshouse (three) and field trials (one). The treatments were combination of three levels of Zn with: (i) three levels of P, (ii) two levels of lime (Experiment 2=Zn×P×lime; experiment 3= Zn×lime; experiment 4=Zn×P and experiment 5=Zn×lime) . Sequential extraction of six soil series for Zn fractions indicated that most of the Zn occurred in the residual fraction (around 70%) and the water soluble plus exchangeable (WE) fraction was less than 5% of the total Zn content. The WE fraction had a highly significant positive correlation (0.73**) with organic bound Zn (Org) and significant positive correlations with soil clay content (0.41**) and CEC (0.48**). The glasshouse trials showed that application of Zn significantly increased the dry matter of shoots, stem, total dry matter and total grains weight. The same parameters also increase when P and lime were added to the soils, but their application decreased the Zn status of the soil and Zn content of plant tissues. The best Zn levels were 5 kg ha-1 for Kundur and Tepus , and 10 kg ha-1 for Telemong soil series. The same results were found in non-limed and limed soil. The highest grain (GY) and straw yield (SDW) were obtained in TPS at 5 kg Zn ha-1 level, which were 56 and 23% more than untreated Zn pots. Also, the maximum increase in GY and SDW were recorded at 10 kg Zn ha-1application with 68 and 25% in KDR, and 63 and 33% for TLM soil series, respectively. The highest total, straw, and grain Zn uptake were 11.46, 4.45 and 1.54 mg pot-1 in TPS by 10 kg Zn ha-1 application, respectively. The highest Zn increase in grain due to Zn application was obtained in TPS soil series (1.68%), (1.10%) for KDR and 1.43% for TLM in glasshouse trials, whereas the decrease in grain Zn due to lime application was recorded for TPS (31%) and TLM (14%). In field trials, application of lime and Zn increased the rice yield about twofold (6.84 ton ha-1). Also, the Zn in grain increased 30% in comparison with untreated plots. But in all experiments, lime and P application across the Zn levels reduced not only the roots, leaves, stems, panicles and grains Zn contents, but also the Zn use efficiency. Therefore, the proper management of P, lime and Zn application in paddy fields of the Zn defeciet soils in the tropic can improve rice growth and its Zn biofortification.